"I Know How You Feel": Preschoolers' emotion knowledge contributes to early school success. (October 2015) - Denham, Susanne A; Bassett, Hideko H; Brown, Chavaughn; Way, Erin; Steed, Jessica
Differences in emotion knowledge by children's age, gender, and socioeconomic risk status, as well as associations of emotion knowledge with executive control, social competence, and early classroom adjustment, were investigated. On emotion knowledge, 4- and 5-year-olds scored higher than 3-year-olds, with girls showing this effect more strongly. Socioeconomic risk status and emotion knowledge were negatively related. Furthermore, executive control was found to contribute to variance in emotion knowledge. Even with age, gender, socioeconomic risk status, and executive control covaried, emotion knowledge contributed to variance in social competence. Given these covariates, it contributed only indirectly to classroom adjustment, via its contribution to social competence. Implications are discussed for practice and policy attention to emotion knowledge within social–emotional curricula and assessment, targeting the period between ages 3 and 4 years, as well as children living in poverty.